Night Sky Tourism Destinations: Raising Awareness of Community Potential Score - Sulisworo, Dwi; Maryani, Ika; Okimustava,; Pramudya, Yudhiakto; Nurnugroho, Burhanudin Arif (Advances in Social Sciences Research Journal, 2022)
Argodadi Village is an area with tourism potential due to the construction of the Yogyakarta International Airport route to Yogyakarta. One of the tourism potentials in this area is the Night Sky Tour which explores celestial objects. However, this potential has not been developed due to residents' limitations in tourism management, skills in astronomy and using telescopes, and marketing of tourism services. This activity aims to develop tourism destinations based on community participation in collaboration with the Tourism Office, sub-district and local village governments, universities, and other communities. Tour services include camping activities, observing celestial bodies at night and in the morning, and team building targeting children in the 5th to 8th grade-students. Promotions carried out through social media are relatively effective by gaining the interest of 54 participants from a quota of 35 participants. The questionnaire data found that the stakeholders showed optimism in this destination of 5.31 out of a scale of 7. Meanwhile, the Night Sky Tour activity participants responded with a satisfaction response of 4.82 out of a scale of 7. The inaugural activity of this Night Sky Tour needs to be followed up in several proposed agendas to maintain continuity.